The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.4018/ijaci.2020010101
|View full text |Cite
|
Sign up to set email alerts
|

Taxonomy on Ambient Computing

Abstract: The rise of Internet-of-Things, Cloud infrastructure, and intelligent home solutions has resulted in the growth of Ambient Computing over the past decade. This article is an attempt to cluster the multi-dimensional research in ambient computing into relevant nodes. The author proposes a taxonomy in ambient computing, creating a logical arrangement of such nodes. An algorithm based on the cosine similarity function for calculating the distance between two ‘author keywords' has been used to spawn the inter-nodal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…In our study, we have observed that apart from life and life balance (related terminology with search term: work-life balance) covid having higher link strength than the rest of the items. Fig 12 . shows the density visualization based on the total link strength (Mu et al (2019), Mas-Tur et al (2021), Du et al (2021), Baier Fuentes et al (2018, Sengupta et al (2020), Ashour et al (2018), Tuan et al (2018), Li et al (2017), Hore et al (2016), ).…”
Section: Resultsmentioning
confidence: 99%
“…In our study, we have observed that apart from life and life balance (related terminology with search term: work-life balance) covid having higher link strength than the rest of the items. Fig 12 . shows the density visualization based on the total link strength (Mu et al (2019), Mas-Tur et al (2021), Du et al (2021), Baier Fuentes et al (2018, Sengupta et al (2020), Ashour et al (2018), Tuan et al (2018), Li et al (2017), Hore et al (2016), ).…”
Section: Resultsmentioning
confidence: 99%